Microbial Resources and Innovation in the Wine Production Sector - Berbegal, C.; Spano, G.; Tristezza, M.; Grieco, F.; Capozzi, V. (South African Journal of Enology and Viticulture, 2017)
Microbial starter cultures represent a fundamental level of innovation in the wine sector. Selected yeast strains are routinely used to achieve the needed biomass preparation to accelerate and steer alcoholic fermentation in grape must. The use of starter cultures to induce malolactic fermentation in wine relies on the characterisation and propagation of suitable strains of lactic acid bacteria. Furthermore, the selection of new strains, the renewal of management of microbial resources and new technologies allow continuous improvements in oenology, which may increase the beneficial aspects of wine. In this review, with the aim to stimulate microbial-driven, consumer-oriented advances in the oenological sector, we propose an overview of recent trends in this field that are reported by following the classical separation into ‘product innovation’ and ‘process innovation’. Hence, we shall highlight i) the possible positive innovative impacts of microbial resources on the safety and the sensorial and functional properties of wine (product innovation) and ii) the potential microbial-based improvements allowing the reduction of time/costs and the environmental impacts associated with winemaking (process innovation).